Milk Safety Assessment, Isolation, and Antimicrobial Susceptibility Profile of Staphylococcus aureus in Selected Dairy Farms of Mukaturi and Sululta Town, Oromia Region, Ethiopia - Sema Regasa; Shimelis Mengistu; Ashebr Abraha (Veterinary Medicine International)
A cross-sectional study was conducted to estimate the prevalence of Staphylococcus aureus in raw milk and swab, to assess the antimicrobial susceptibility profile, milk handling practice, and its associated risk factors in selected dairy farms of Mukaturi and Sululta Town, Oromia Region, Ethiopia. A total of 247 samples collected from dairy farms were examined using standard microbiological techniques. The antimicrobial susceptibility profiles of the isolates were also investigated. The possible risk factors for Staphylococcus aureus contaminations in milk were evaluated through a structured questionnaire. Overall, 16.6% (n= 41) of the samples were positive for S. aureus. The prevalence of S. aureus was 15.3% from udder milk and 25%, 20%, and 10% from milkers’ hand, milking bucket, and drying towel swab, respectively. The prevalence of Staphylococcus aureus in milk showed statistically significant variation with respect to age (p≤ 0.001), parity (P≤ 0.001), drainage condition of milking area (P=0.035), study sites (P=0.035), and management system (P=0.035). Majority of the isolates were found resistant to penicillin G (97.6%) and amoxicillin (43.9%). According to this study, 12/28(42.9%) Staphylococcus aureus positive raw milk samples had 104-105cfu/ml S. aureus count, which is above the recommended level for human consumption. 47.1% of milking persons store milk at room temperature temporarily (between 6 and 12 hrs) till transport to collection center with no means of cooling aid. From consumers 25.6% had no health risk associated with raw milk consumption or aware of milk borne disease associated with drinking raw milk. Thus, 60.5% of milk users had habit of raw milk consumption. The study revealed a prevalence of S. aureus, poor milk handling practices, raw milk consumption behavior in study area. Proper handling and hygiene decrease milk contamination by S. aureus and make it safe for human consumption.